Traditional Games as English Learning Media for Early Childhood - Novitawati Novitawati; Ratna Purwanti; Herti Prastitasari; Nora Vitriati; Khairati Olfah (UNIB Press, 2022)
Traditional games are games that provide a special color of culture as well as the identity or characteristic of an area that needs to be maintained that aims to stimulate early childhood especially about the recognition of numbers in English.The purpose of this stud ratna.purwanti@ulm.ac.idy was to describe traditional games as a medium in learning English for early childhood. This type of research is qualitative with a phenomenological approach. Data collection methods are interviews, observation and documentation. The research subjects were the principal and class teacher. The data analysis technique used triangulation method (observation, interview and documentation study). The results showed that learning English through traditional games from South Kalimantan (Badaku) in TK Matahariku can (1) increase children's English vocabulary in the form of numbers reach category very active or BSB with 100% and (2) can stimulate children's intelligence in recognizing numbers category very active or BSB with 95%. The implications of using traditional games as a medium for learning English for early childhood provide convenience for teachers and children in the classroom.